Performance of rice cultivars with the use of growth‑regulators in different cropping systems - Grohs, Mara; Marchesan, Enio; Roso, Rodrigo; Formentini, Tiago Constante; Oliveira, Maurício Limberger de (Pesquisa Agropecuaria Brasileira, 2012)
<span lang="EN-US" style="line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The objective of this work was to evaluate the effect of growth‑<span lang="EN-US" style="line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">regulating substances on initial establishment and agronomic performance of irrigated rice cultivars, in different cropping systems. The experiment was carried out in controlled environment and in field conditions, using the cultivars Irga 424 and Irga 425, and the products gibberellic acid, thiamethoxam and Haf Plus. At field, treatments were tested with conventional and pre‑<span lang="EN-US" style="line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">germinated sowing systems. In the controlled environment, the evaluated substances promoted the germination of Irga 425, with an increase of 50% in germination with the use of thiamethoxam and of 39% with Haf Plus and gibberellic acid. In the field, this performance was dependent on the system and the cultivar used. Gibberellic acid caused initial blanching, which reflected in plant height, tiller emission, and deposition of vegetal biomass. Thiamethoxam and Haf Plus stimulated tillering of rice cultivars in both cultivation systems. Although all the products stimulated the number of panicles per square meter, there is no influence on grain yield in the evaluated systems.